'As fit as fiddles' and 'as weak as kittens': the importance of food, water and diet to the Anzac campaign at Gallipoli. Issue 2 (3rd May 2016) - Wishart, Alison
Abstract: The reasons for the allied defeat at Gallipoli in 1915 have been much debated and disputed. Yet one factor which has not been seriously considered is the role of food. This paper argues that food, water and diet played a significant role in the Gallipoli campaign. It provides eight reasons why the provision of food and water at Gallipoli was logistically complex, sometimes unique to the peninsula and warrants special attention. It then goes on to discuss the physical and psychological effects of a monotonous, un-nutritious diet which depleted the immune systems of previously healthy men. The vast majority of the Anzacs quickly succumbed to the infectious diseases spread by the plague of summer flies. Once sick, providing the men with the same unappetising, un-nutritious rations just made them sicker. Gallipoli should be infamous not only for the poorly planned and executed military campaign, but as the place where the Australian Imperial Force evacuated twice as many men for sickness than it did for the treatment of wounds. In other words, the Mediterranean Expeditionary Force (MEF) did a better job of depleting the fighting strength of its own forces than the enemy. One of the main reasons for this was the failure of the MEF to provide its army with a nutritious, palatable diet and sufficient water.